2013
DOI: 10.1158/2159-8290.cd-12-0031
|View full text |Cite
|
Sign up to set email alerts
|

Targeting C4-Demethylating Genes in the Cholesterol Pathway Sensitizes Cancer Cells to EGF Receptor Inhibitors via Increased EGF Receptor Degradation

Abstract: Persistent signaling by the oncogenic epidermal growth factor receptor (EGFR) is a major source of cancer resistance to EGFR targeting. We established that inactivation of two sterol biosynthesis pathway genes, SC4MOL (sterol C4-methyl oxidase-like) and its partner NSDHL (NADP-dependent steroid dehydrogenase-like), sensitized tumor cells to EGFR inhibitors. Bioinformatics modeling of interactions for the sterol pathway genes in eukaryotes allowed us to hypothesize, and then extensively validate an unexpected r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 56 publications
2
85
0
Order By: Relevance
“…4C). Silencing of CYP51A1, an enzyme acting upstream of NSDHL in the cholesterol synthesis pathway that prevents accumulation of MAS (Sukhanova et al, 2013), reversed the upregulation of ABCA1 in NSDHL-deficient cancer cells (Fig. 4D) supporting the idea that upregulation of MAS metabolites is important in triggering LXR activation.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…4C). Silencing of CYP51A1, an enzyme acting upstream of NSDHL in the cholesterol synthesis pathway that prevents accumulation of MAS (Sukhanova et al, 2013), reversed the upregulation of ABCA1 in NSDHL-deficient cancer cells (Fig. 4D) supporting the idea that upregulation of MAS metabolites is important in triggering LXR activation.…”
Section: Resultsmentioning
confidence: 64%
“…We evaluated two additional models. Using a series of SCC61 carcinoma cells in which the expression of NSDHL or SC4MOL was silenced with specific shRNAs, versus vector controls (Sukhanova et al, 2013), we found depletion of these proteins increased levels of cleaved SREBP2 (Radhakrishnan et al, 2008), and expression of ABCA1 (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EGF receptor (EGFR) may be pivotal in these skin changes, as similarities are observed in mice and humans with EGFR pathway perturbations. Moreover, accumulation of MASs through inactivation of SC4MOL and NSDHL reduces EGFR expression and signaling (10).…”
Section: Intermediates In Cholesterol Synthesis As Physiological Regumentioning
confidence: 99%